The science of war defense budgeting, military technology, logistics, and combat outcomes - O'Hanlon, Michael E. (Princeton University Press, 2009)
Michael O'Hanlon provides undergraduate and graduate students with an accessible yet rigorous introduction to the subject. Drawing on a broad range of sources and his own considerable expertise as a defense analyst and teacher, he describes the analytic techniques the military uses in every crucial area of military science. O'Hanlon explains how the military budget works, how the military assesses and deploys new technology, develops strategy and fights wars, handles the logistics of stationing and moving troops and equipment around the world, and models and evaluates battlefield outcomes. His modeling techniques have been tested in Iraq and Afghanistan, including the methods he used to predict higher-than-anticipated troop fatalities in Iraq--controversial predictions that have since been vindicated.